CLIENTS' AND CAREGIVERS' EXPERIENCES OF A COMMUNITY-BASED SUPPORT SERVICE PROGRAM "BETTER AT HOME". (11th November 2018) - Wada, M; Chaudhury, H; McGrail, K; Whitehurst, D; Lalji, K
Abstract: This qualitative study explored older adult clients' and family caregivers' experiences of the Better at Home (B@H) program, a non-medical home support service program to foster older adults' independent living in their homes in British Columbia, Canada. Forty clients (age 60+) of the program and 14 informal caregivers were recruited in Metro Vancouver and North Okanagan who participated in semi-structured interviews (April 2016 - May 2017). The interviews with clients elicited their experiences of B@H regarding its impact on their levels of health, independence and community participation. The interviews with family caregivers explored their perceptions of how B@H influenced the older adult clients as well as themselves regarding functioning and social engagement. Using a thematic analysis approach, we analyzed clients' and caregivers' interviews separately and compared the findings between the two groups. The findings revealed: 1) clients' levels of satisfaction with B@H (e.g., accessibility, affordability, quality of services); 2) clients' and caregivers' perceptions of the impact of B@H on clients' physical and mental health (e.g., saving personal energy, reduced stress) and social participation; 3) the impact of B@H on caregivers' health (e.g., decreased pressure) and social engagement (e.g., time to pursue their own goals); and 4) suggestions to enhance and advance B@H in supporting older adults' independent living in their homes and communities. The findings indicate that while both clients' and caregivers' experiences of B@H were generally positive, there is a diversity of client needs. Implications for the program will be discussed.